Testosterone regulates birdsong in an anatomically specific manner. (February 2017) - Alward, Beau A.; Rouse, Melvin L.; Balthazart, Jacques; Ball, Gregory F.
Abstract : The functions of birdsong include attracting a mate and repelling competitors. It is therefore not surprising that, in males in the temperate zone especially, birdsong is often produced in the context of reproduction. Testosterone of gonadal origin increases during the reproductive phase of the annual cycle and can significantly influence song production as well as song development via effects on song crystallization (testosterone secretion at the time of sexual maturity is essential for full crystallization to occur). In males, testosterone of gonadal origin can exert its effects in the brain on song and other reproductive behaviour via its oestrogenic and androgenic metabolites. The widespread distribution of nuclear androgen receptors in the song system and the occurrence of oestrogen receptors in one key forebrain nucleus in certain species as well as the presence of both receptor types in the diencephalon and the midbrain raises questions as to where and how testosterone is exerting its myriad effects on song. By selectively implanting testosterone into specific brain regions of castrated male canaries, Serinus canaria, we have identified the medial preoptic area as a critical site for the induction of a generalized increase in motivation that includes the motivation to sing. Testosterone action in the forebrain song nucleus HVC in contrast increases song stereotypy. Canaries receiving testosterone in the preoptic area and HVC sing stereotypic songs but at a much lower amplitude, indicating that testosterone's effects on amplitude are regulated elsewhere in the brain or the periphery. The lateral part of the magnocellular nucleus anterior nidopallium (LMAN) is a song nucleus that expresses a high density of androgen receptors and plays a role as a song variability generator during song learning. When adult female canaries are treated with testosterone, their song becomes more complex. Lesions to LMAN attenuate these effects on adult behavioural change, suggesting that testosterone may act in LMAN during song ontogeny to modulate changes associated with song crystallization. These anatomically specific effects illustrate how a single hormone can coordinate changes in many aspects of a complex behaviour to facilitate successful reproduction. Highlights: Many aspect of song behaviour are profoundly regulated by testosterone. Testosterone has distinct effects on song based on where in the brain it acts. Testosterone promotes the motivation to sing by acting in the preoptic area. Testosterone enhances song quality by acting in the song control nucleus HVC. LMAN lesions block testosterone-induced song masculinization in female canaries.